Rapid prototyping of micropillars using digital light process 3D printing technique - Nur Aliyah Alwani Mohd Nazam; Jumril Yunas; Abdul Hafiz Mat Sulaiman; Muhamad Ramdzan Buyong; Azrul Azlan Hamzah (Penerbit Universiti Kebangsaan Malaysia, 2020)
In this paper, we discuss a technique to fabricate a three-dimensional (3D) printed micropillars structure of microfluidic system. The developed system consists of microchannels, chambers, and micropillars. The creation of arrays of pillars were the focus of the study. The structure is fabricated using a 3D printing technique called Digital Light Process (DLP). In this paper, we examine the potential use of the 3D printing approaches for the fabrication of microfilter and micromixer devices integrated with microfluidic channels. Our 3D printing process shows that micropillars with diameters between 200 and 400 µm can be fabricated using a DLP 3D printer machine by optimizing the preparation process and post processing parameters. Later, SEM analysis shows that micropillars with high aspect ratio and straight side wall were achieved. The DLP 3D printer is the most suitable and reliable technique that can produce the smallest dimension compared to other types of 3D printer that shows a promising method for the rapid prototyping of microfluidic devices for biomedical application.